Marriage Readiness of Emerging Adulthood - Karunia, Nurlita Endah; Rahaju, Soerjantini (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2019)
Marriage readiness is one of the keys to marital satisfaction. Emerging adulthood has some thoughts about that bassist Reviews their evaluation criterion of marriage readiness. It is essential to describe the approach of marriage readiness on emerging adulthood and understand emerging adulthood's evaluation of Reviews their marriage readiness. On the other hand, it is necessary to identify the differences in marriage readiness from a gender perspective. Quantitative This is an exploratory study, using 500 college students, aged between 18-25 years old, and consisted of 190 men and 390 women. The questionnaire using Criterion of Marriage Readiness to examine the criterion that important to marriage readiness (33 items, Cronbach alpha 0.917) and the level of emerging adulthood's preparation for marriage (33 questions, Cronbach alpha 0.946). The questionnaire using the criterion from Ghalili's study (2011). There are some results of this study. First, emerging adulthood evaluates Themselves are ready for Marriages, but not so prepared for marriage. They score higher places on the moral and mental criterion that Considered necessary for marriage readiness. This finding is somewhat consistent with the result of the preparedness of Marriages. Emerging adults have a higher score of preparation of Marriages in moral and mental criterion. There are significant differences between men and women in the standard of Marriage readiness married (sig 0.001, P <0.05) and the level of preparedness to marriage (sig 0.008, P <0.05). These findings are useful for government institutions, parents, and adults emerging as the basis of consideration of emerging adulthood's decision to marry.